Factors that determine the price of game - P. van der Merwe; M. Saayman; W. Krugell (Koedoe: African Protected Area Conservation and Science, 2004)
Fraser (1999) forecasts that South Africa’s tourism industry will grow by more than 5.5 % between 1998 and 2010, which is better than the predicted 4.1% for the global market. It is estimated that arrivals will increase from six million international tourists in 2000 to 30.5 million in 2020 (WTO 2001). The African continent can triple the size of its tourism industry by 2020 if proper efforts are made. This will result in forecast tourist arrivals of 77.3 million to Africa.